Food availability modulates the effects of maternal antibodies on growth and immunity in young feral pigeons. (8th April 2015) - Ismail, A.; Jacquin, L.; Haussy, C.; Perret, S.; Gasparini, J.
Abstract : It is now widely acknowledged that mothers can transfer their own immune experience to their progeny through the allocation of specific maternal antibodies (hereafter referred as MatAb) that can shape offspring phenotype and affect their fitness. However, the importance of environmental variability in modulating the effects of MatAb on offspring traits is still elusive. Using an experimental approach, we investigated how food availability interacted with MatAb to solve the trade‐off between humoral immunity and growth in young feral pigeons Columba livia . Results show that the inhibitory effect of MatAb on the humoral response of chicks was detected regardless of the food treatment. In addition, body mass growth was higher in chicks receiving lower amounts of maternal antibodies but only in chicks of the ad libitum food treatment. This contradicts previous studies and suggests that the transfer of MatAb could entail some costs for chicks and reduce their growth. Taken together these results reinforce the idea that the maternal antibodies play a central role in shaping offspring life‐history traits but that their adaptive value is highly dependent on the environmental context in which they are transmitted by the mother.